Evaluasi Program Pendidikan Inklusi, Fasilitas Pendukung, dan Keterlibatan Orang Tua di SD Islam Al- Izzah Purwokerto - Cita, Ajeng Dwi; Lestari, Anis Suci; Haq, Mochammad Izzul; Fadhilah, Nisa Nur (J-PGMI: Jurnal Pendidikan Guru MI, 2025)
The aim of this research is to evaluate how inclusive education is implemented at Al-Izzah Islamic Elementary School, Purwokerto. This research concentrates on three main components of inclusion implementation: the programs implemented, the supporting facilities available, and the role of parents in supporting the success of inclusive education. Analysis of school inclusive education policies, interviews with heads of inclusion programs, and field observations were the methods used. The research results show that Al-Izzah Purwokerto Islamic Elementary School has implemented an inclusion program, which includes curriculum changes, special teaching strategies, and the formation of a support team to help students with special needs learn. However, there are some shortcomings in terms of physical facilities and adaptive learning media, which need to be improved to make them more accessible and help students with special needs learn better. Apart from that, this research found that parents' involvement in their children's inclusive education was good. Most parents are already involved in school activities and programs related to inclusive education. The results of this research show that schools must continue to improve physical facilities and adaptive learning media, and can always develop programs that can increase parental involvement and understanding about inclusive education. Thus, inclusive education at Al-Izzah Purwokerto Islamic Elementary School is expected to increase cooperative communication between the school and parents to help children learn well and it is also hoped that the learning process will run more efficiently while providing the best benefits for all students, both those who have special and regular needs.